2019
DOI: 10.1371/journal.pone.0217652
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-582-5p suppresses non-small cell lung cancer cells growth and invasion via downregulating NOTCH1

Abstract: Non-small cell lung cancer (NSCLC) is the most common cancer worldwide. MicroRNAs have been shown to be correlated with biological processes of various tumors. In this study, we observed that the expression of miR-582-5p was lower in NSCLC tissues than that in para-carcinoma tissues. Ectopic expression of miR-582-5p significantly inhibited NCI-H358 cell proliferation and invasion. Knockdown of miR-582-5p showed the opposite results, with cell growth rate and the invasive capacity of PC-9 cells enhanced. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
5
19
0
Order By: Relevance
“…Herein, we focused on the role of miR-582-5p in NSCLC. It was shown that miR-582-5p suppressed the progression of NSCLC via mitogen-activated protein kinase kinase kinase 2 (MAP3K2) [20], and that miR-582-5p restrains the proliferation and invasion of NSCLC cells via Notch homolog 1, translocation-associated (NOTCH1) [21]. In the present study, we found a new regulatory mechanism involving miR-582-5p in NSCLC.…”
Section: Introductionsupporting
confidence: 49%
See 3 more Smart Citations
“…Herein, we focused on the role of miR-582-5p in NSCLC. It was shown that miR-582-5p suppressed the progression of NSCLC via mitogen-activated protein kinase kinase kinase 2 (MAP3K2) [20], and that miR-582-5p restrains the proliferation and invasion of NSCLC cells via Notch homolog 1, translocation-associated (NOTCH1) [21]. In the present study, we found a new regulatory mechanism involving miR-582-5p in NSCLC.…”
Section: Introductionsupporting
confidence: 49%
“…LncRNA XLOC_006390 potentiates the malignancy of cervical cancer cells through miR-331-3p and miR-338-3p sponging [34]. MiR-582-5p serves as a tumor suppressor in many cancers, including hepatocellular carcinoma, colorectal carcinoma, gastric cancer and NSCLC [20,21,[35][36][37]. MiR-582-5p suppresses the proliferation and metastasis of colorectal cancer cells via Ras-related protein Rab27a [36], and impedes the proliferation and motility of NSCLC cells [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hub genes and their corresponded target miRNAs are presented in Table . Finally, 31 miRNAs, whose functions were correlated with tumor progression (Chang et al, ; Chang et al, ; Chen et al, ; Gao et al, ; Gu et al, ; Han et al, ; He et al, ; Kucuksayan et al, ; Li, Ma, Zhang, Ji, & Jin, ; Li, Ran, et al, ; Li & He, ; Li, Fu, et al, ; Li, Cui, Li, Zhang, & Li, ; Liu et al, ; Liu, Liu, Deng, et al, ; Liu, Liu, & Lu, ; Liu, Liu, Zhang, Tong, & Gan, ; Liu, Miao, et al, ; Luo et al, ; Tang et al, ; Wang et al, ; Wang, Cao, Su, Li, & Yan, ; Wu et al, ; Wu, Mo, Wan, Dan, & Hu, ; Xia, Jing, Li, & Lv, ; Xu et al, ; Zeng et al, ; Zhang, Hao, et al, ; Zhang et al, , ; Zhu et al, ), drug resistance (Bian et al, ; Gao et al, ; Lin, Xie, Lu, Hu, & Chang, ; Pan, Chen, Shen, & Tantai, ; Su et al, ; Xu et al, ; Zhou, Wang, & Feng, ), radiosensitivity (Liu, Li, & Gao, ), recurrence (Sim et al, ) or autophagy (Pan et al, ) in lung cancer, were identified (Table ).…”
Section: Resultsmentioning
confidence: 99%